CATALYSING GROWTH THROUGH BOARD MEMBERS ENGAGEMENT IN STRATEGY EXECUTION - Muhamad Roslan MUHAMAD YUSOFF; Ahmad Rahman SONGIP; Mas Bambang BAROTO; Aini Suzana ARIFFIN (Studia Universitatis Babeş-Bolyai Negotia, 2016)
Strategy Management, a widely spoken attribute among organizations, exhibits their repute on a global platform. Employing strategy to shape the organizational growth is an approach which demands significant research, experience, intelligence and foresight to ensure its success at each level within the organization. The traditional perception of strategy designing reflects the board as the sole responsible authority, with keen awareness of organizational aspects, which include resources, finances, limitations and challenges. Later, when the strategy is rolled out to management and executive levels; many of the strategies lead to a messy, disorderly and disjointed process. Reason behind poor strategy management in the execution phase is the lack of leadership initiatives by board members after strategy planning. This study reviews the role of board members in strategy formulation and challenges faced at Malaysian Government Link Companies (GLCs) particularly in the service sector. It is also looking at minimizing the strategy failure by enhancing the role of board members at deep-rooted levels of strategy execution. In order to capture the rich data from GLCs, this research adopts qualitative approach in its efforts to explore a new dimension in strategy execution. Often challenged by the human perspectives at different levels, the higher lever board tends to limit their scope towards visualizing and rolling out a strategy. This paper addresses the conventional strategy management archetype and introducing the board room engagement at multiple levels, to make certain the organizational growth not for a short span but in a long run, hence ensuring organization sustainability.